Developing digital transformation strategies from SWOT-TOWS analysis for higher education institutions in Beijing, China - Chen, Huanli; Tuntinakhongul, Ampapan (Edelweiss Applied Science and Technology, 2026)
This study aimed to develop digital transformation strategies for higher educational institutions in Beijing, China, by applying a SWOT analysis in which educational administration was examined as the internal environment and PEST factors as the external environment. The purpose was to advance inclusive learning, strengthen knowledge exchange and partnerships, and enhance data-driven education. The study adopted a qualitative research design and collected data through semi-structured interviews with nine experts. The data were analyzed using content analysis and subsequently synthesized through a TOWS matrix to generate strategic directions. The findings identified 36 strategies across four categories: SO, ST, WO, and WT. The major strategies included leadership support, system integration, student-centered services, collaborative digital platforms, data governance, and staff capacity building. These strategies have the potential to improve accessibility and administrative coordination, strengthen collaboration with external stakeholders, and support evidence-based decision-making. The study offers a practical strategic framework for university leaders, administrators, and policymakers, while also providing a foundation for future research on digital transformation in higher education.